Aircraft structure for engineering students - Megson, Thomas H. G (Butterworth-Heinemann, 2006)
Designed to help students get a solid background in structural mechanics and extensively updated to help professionals get up to speed on recent advances. Designed and structured to provide a solid foundation in structural mechanics, Mechanics of Aircraft Structures, Second Edition includes more examples, more details on some of the derivations, and more sample problems to ensure that students develop a thorough understanding of the principles.